How a municipality in Nepal is creating a model for local groundwater governance - KC, Sumitra; Niroula, Aayush; Mishra, Anuj; Khadka, Manohara (International Water Management Institute, 2025)
The International Water Management Institute (IWMI) is working with the Barahathawa Municipality in the Madhesh Province of Nepal to enhance local groundwater governance. This video captures Barahathawa’s journey from research to action, bringing together diverse actors and stakeholders for inclusive and sustainable groundwater management.